Wind action on water standing in a laboratory channel - Hidy, G. M., author; Plate, E. J., author; National Center for Atmospheric Research, publisher (Colorado State University. Libraries, 1965)
The processes of wave and current development resulting from wind action on initially standing water have been investigated in a wind-water tunnel. The mean air flow over wavy water was examined along with the variation of several properties of the water motion with fetch, water depth, and wind speed. Measurements of phase speed and length of significant waves, the standard deviation of the water sur face, the average surface drift, the autocorrelation of surface displacement and the frequency spectra of the wind waves are reported. The experimental results indicate that (a) the air motion in the channel follows a three dimensional pattern characteristic of wind tunnels of rectangular cross-section; (b) the wind waves generated in the channel travel downstream at approximately the same phase speed as gravity waves of small amplitude, provided the effect of the drift current is taken into account; (c) the average drag coefficients for the action of the wind on the water surface increase with increasing wind speed, and these data are essentially the same as the results of previous investigators; (d) the autocorrelations of surface displacement and frequency spectra are consistent with the visual observations that the wind waves in the channel consist of nearly regular primary waves on which are superimposed smaller ripples; (e) energy in the high frequency range in the spectra tends to approach an equilibrium distribution rather quickly while the lower frequency components initially grow exponentially with increasing fetch but, later, tend to reach a state of equilibrium; and (f) a similarity shape for the frequency spectra developed.
CEP6566-GMHEJP14a, CER65GMH-EJP40a.
NCAR preprint-memo, PM # 135.
Keywords: Winds; Water currents